MODEL OF PROCEDURES CASH DISBURSEMENT SYSTEM FOR PURCHASING ASSETS IN VILLAGE ACCOUNTING SYSTEMS - Khozin Arief (NATAPRAJA, 2020)
This study aims to create a procedure model of cash expenditure system assets in the village accounting system to be used in villages throughout Indonesia so that the administration of village accounting can be run accountable, transparent, can be accounted for according to applicable laws. Based on the preliminary interview conducted by the researcher to the village officials, it was found that in the implementation of the procedure for issuing cash on asset purchases, procedural errors sometimes occurred in the village accounting administration due to the incomplete documentation of the procedure model. This procedural error led to irregularities in village financial managers. Therefore we need a well-documented and complete procedure for cash disbursement procedures for asset purchasing as a guideline for administering village accounting. The methodology of this research was carried out by data collection techniques through interviews, observation, and system documentation carried out in the villages of Parongpong District, West Bandung Regency, West Java Province, with stages starting from planning, surveying, analyzing and designing systems. In designing this village accounting procedure model, the author follows applicable government laws and regulations and literature studies on village accounting